1987
DOI: 10.1038/326400a0
|View full text |Cite
|
Sign up to set email alerts
|

The T lymphocyte glycoprotein CD2 binds the cell surface ligand LFA-3

Abstract: CD2 (known also as T11 (ref. 1), LFA-2 (ref. 2) and the erythrocyte rosette receptor (ref. 3] is a functionally important T lymphocyte surface glycoprotein of relative molecular mass 50,000 to 58,000 (Mr 50-58 K) which appears early in thymocyte ontogeny and is present on all mature T cells. Monoclonal antibodies to CD2 inhibit cytotoxic T-lymphocyte (CTL)-mediated killing by binding to the T lymphocyte and blocking adhesion to the target cell. Such antibodies also inhibit T helper cell responses including ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
226
2
2

Year Published

1990
1990
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(234 citation statements)
references
References 24 publications
4
226
2
2
Order By: Relevance
“…According to this concept, the known ligands of the CD2-related proteins are represented by one or another member of this molecular family. In particular, it has been shown that these molecular interactions are either heterophilic, such as CD2/CD58, CD2/CD48, and CD244/ CD48, or homophilic, such as CD150/CD150, CD84/ CD84, and CS1/CS1 [22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to this concept, the known ligands of the CD2-related proteins are represented by one or another member of this molecular family. In particular, it has been shown that these molecular interactions are either heterophilic, such as CD2/CD58, CD2/CD48, and CD244/ CD48, or homophilic, such as CD150/CD150, CD84/ CD84, and CS1/CS1 [22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Both heterophilic and homophilic interactions have been described between different members of the CD2 family [22][23][24][25][26][27][28]. We therefore explored the possibility that NTBA may recognize one or another member of this family.…”
Section: Ntba Mediates Homophilic Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD2 mediates adhesion by binding to its counterreceptor CD58 in humans (Selvaraj et al, 1987). CD2-mediated adhesion facilitates T cell recognition of antigens by the T cell receptor (Moingeon et al, 1989b: Koyasu et al, 1990 J ( w N ) , and J(w"), spectral density function derived at zero, nitrogen, and proton frequencies, respectively; Jeg(0), in the absence of exchange its value equals J(0); Juvg(wH,).…”
Section: Introductionmentioning
confidence: 99%
“…T112 and T113 epitopes of CD2 and the consequent f cell activation process reflects an interaction of naturally occurring ligands involved in physiological T cell activation. Indeed there is compelling evidence that the LFA-3 molecule is a tigand fortheTIli epitope of CD2 both for T cell adhesion (6)(7)(8) and T cell activation (8)(9)(10). The identity of the ligands for the T112 and T113 epitopes remains to be established.…”
Section: Introductionmentioning
confidence: 99%